N-acetyltransferase 2 genetic polymorphisms and anti-tuberculosis-drug-induced liver injury: a correlation study - Cheng, Fang; Jiang, Xian-Gao; Zheng, Shi-Lin; Wu, Te; Zhang, Qiang; Ye, Xin-Chun; Liu, Saiduo; Shi, Ji-Chan (Frontiers in Pharmacology, 2023)
Background: Considering the genetic characteristics of people with anti-tuberculosis (TB)-drug-induced liver injury (ATDILI), genetic factors and their consequences for treatment need to be studied. Objective: The correlation between N-acetyltransferase 2 (NAT2) genetic polymorphisms and ATDILI was analysed. Methods: In this study, the liver and coagulation functions of 120 patients with TB were monitored dynamically for at least 3 months. The genetic polymorphisms of patients were detected by pyrosequencing, and the acetylation types of liver damage and the distribution of NAT2 genetic polymorphisms were compared and analysed. Results: The results showed that there were significant differences in the distribution of alleles and acetylation types among different groups (p < 0.05). In patients with grade 4 liver injury (liver failure), any two alleles were included, i.e., *6 and *7. Specifically, patients with fast acetylation genotypes accounted for 42.4% (14/33), those with intermediate acetylated genotypes accounted for 55.2% (32/58), and patients with slow acetylation genotypes accounted for 65.5% (19/29). Conclusion: Patients with slow acetylation genotypes had higher rates of liver failure and liver injury than those with intermediate and fast acetylation genotypes, and patients with slow acetylation genotypes containing any two alleles (*6 and *7) had a higher rate of liver failure than those with other alleles. In summary, the time of liver injury in patients with slow acetylation genotypes was earlier than the total average time, and the time of liver function recovery in patients with fast acetylation genotypes was shorter than the total average time.